BEBERAPA ASPEK BIOLOGI REPRODUKSI IKAN DOMINAN SEBAGAI DASAR PENGELOLAAN SUMBERDAYA IKAN DI PESISIR PANTAI PAYUM KABUPATEN MERAUKE - Norce Mote; Rosa D. Pangaribuan (Universitas Musamus, Merauke, Papua, 2015)
Coastal areas are particularly vulnerable to environmental degradation, in the other hand this area is rich in fishery resources, like fish, crustaceans and molluscs. This study aims to assess aspects of biology reproduction of fish at coastal area of Payumb, such as sex ratio, an index of gonad maturity, the maturity level of gonads, fecundity and spawning type. The study was conducted over three months start of September to November 2014 at the coast Payum. Sampling was conducted at three stations, there are Muara Kali Lepro, Awaba and Bandiamo and using drag nets and gill nets with mesh size 1, 11/2 and 2 inches as a fishing gear. The sex ratio of Mugilidae are not balance, the value of IKG and TKG are vary each month.